Hedges Analysis in British Council Teacher Podcast: How Can I Use Different Languages in My Teaching? - Juwantoro, Ario; Setyawan, Agustinus Hary (EDULIA: English Education, Linguistic and Art Journal, 2024)
This research looked into how hedges were used in the British Council Teacher Podcast. How can I use different languages in my teaching? This research set out to 1) characterize the language characteristics of hedges and 2) examine the roles that hedges play in conversation. Because this study aims to provide explanations, the qualitative method is employed. The data consisted of utterances made by the podcast participants—Chris, Sue, Mei, and Tony—that indicated the use of hedges. Through the examination of 40 hedging instances, the research identified various types of hedges, with modal lexical verbs being the most frequently used (20%), followed by approximators, introduction phrases, and adjectival/adverbial modal phrases (each at 17.5%). "If" clauses (12.5%) and compound hedges (15%) were also prevalent, showcasing the speakers’ strategic use of linguistic devices to express uncertainty, manage interpersonal relationships, and foster engagement. The findings demonstrate that hedges serve as a critical tool in discussing sensitive topics, such as language policies in education, allowing the speakers to present their views in a flexible and adaptable manner. This research highlights the important role hedging plays in maintaining politeness, reducing imposition, and creating a collaborative conversational environment, particularly in discussions about teaching practices and multilingualism. Keywords: British Council Teacher Podcast, Function of hedges, Hedges Pragmatics, Types of hedges